Confirmation of Structure, Geometry and symmetry of [Co(EDTA)]- Ion by Determining Force Constants - Balasubramanian, N.; Venkatachalam, T. (Asian Journal of Chemistry, 2010)
A simplified procedure was proposed by the authors for the synthesis of sodium ethylenediaminetetraacetate cobaltate(III). Adopting the structural parameters from the data presented by Weakliem and Hoard, force constants were evaluated for the complex ion [Co(EDTA)]–. The data were compared with the force constants reported for similar complex ions. However discrepancies were observed for some bonds such as Co—N in two different environments. A possible explanation was offered by the authors to confirm the octahedral structure of [Co(EDTA)]– ion.